Manajemen Pembelajaran Pendidikan Al-Islam di SMA Muhammadiyah - Itsnaini Novi Imamiyah; Istikomah Istikomah (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
This study aims to determine the learning management of Al-Islam education at SMA Muhammadiyah 2 Surabaya by focusing on 4 sub-topics of discussion which include planning, organizing, implementing, and evaluating. This study uses a qualitative research method with a case study approach. Data collection techniques in this study are observation, interviews, and documentation. The techniques of analysis and interpretation of data in this study are data reduction, data presentation, and data verification. Data sources in this study include primary data sources where the data is obtained from informants when making observations at the research location. While secondary data sources are obtained from articles, theses, and journals that support primary data sources. The results of this study indicate that the learning management of Al-Islam education at SMA Muhammadiyah 2 Surabaya has been carried out following the learning mechanism and is conducted properly based on the learning objectives that have been set. To achieve all aspects Of learning management al Islam education is very dependent on the commitment and capability of educators towards education management itself.